The role of angiogenesis in melanoma: Clinical treatments and future expectations - Zhuzhu Wu; Zhuzhu Wu; Yifei Bian; Tianjiao Chu; Yuman Wang; Shuai Man; Shuai Man; Shuai Man; Yongmei Song; Zhenguo Wang; Zhenguo Wang (Frontiers Media S.A., 2022)
The incidence of melanoma has increased rapidly over the past few decades, with mortality accounting for more than 75% of all skin cancers. The high metastatic potential of Melanoma is an essential factor in its high mortality. Vascular angiogenic system has been proved to be crucial for the metastasis of melanoma. An in-depth understanding of angiogenesis will be of great benefit to melanoma treatment and may promote the development of melanoma therapies. This review summarizes the recent advances and challenges of anti-angiogenic agents, including monoclonal antibodies, tyrosine kinase inhibitors, human recombinant Endostatin, and traditional Chinese herbal medicine. We hope to provide a better understanding of the mechanisms, clinical research progress, and future research directions of melanoma.